Caring for alcohol‐intoxicated patients in an emergency department from the nurses' point of view – focus on attitudes and skills. Issue 1 (9th February 2020) - Hakala, Tiina; Kylmä, Jari; Mäkelä, Kaisu‐Leena; Noppari, Eija; Koivunen, Marita
Abstract : Background: Healthcare professionals have a key role in detecting health risks from alcohol use. The earlier the alcohol misuse is identified and addressed, the lower the risk of harm and the need for actual drug treatment. Positive attitudes and high motivation on the part of nurses are needed for achieving success in the care of intoxicated patients. Aim: The aim of the study was to describe nurses' skills to care for and attitudes towards the care of patients with alcohol intoxication in emergency departments (EDs). Method: The data were collected from nursing staff who participated in online training related to the care of alcohol‐intoxicated patients in the EDs (N = 20, n = 17). As part of the training, nurses wrote two essays. The essays made up the data of this study which were analysed using inductive content analysis. Results: Three main categories emerged from the nurses' descriptions of their skills in caring for and attitudes towards the care of patients with alcohol intoxication: nurse's lack of commitment to intoxicated patient care; nurse's commitment to intoxicated patient care; and nurse's skills in intervention methods. Conclusion: Many different factors influence nurses' commitment or lack of commitment in the care of intoxicated patients. Nurses' attitudes and skills are linked to the success of care of intoxicated patients in ED. Implications for nursing of alcohol‐intoxicated patients: Increasing awareness of alcohol‐related issues seems to help nurses to understand better the situation of a patient with alcohol intoxication, make their attitudes more positive and help them to use the intervention methods.